4 - Reconstruire une « cité métisse ». Migrations européennes, économie touristique et impasses de la valorisation culturelle du patrimoine saint-louisien (Sénégal). - Hélène Quashie (African Sociological Review, 2017)
Going against mainstream research in social sciences which analyzes international mobility related to Africa through South-North and South-South movements, this paper focuses on a particular migration from Europe to Senegal, and more specifically to Saint-Louis city, whose historical island has been listed in the World Heritage of Unesco since 2000. This study is at the crossroads of socio-anthropological analysis of touristic and cultural enhancement of urban landscapes become world heritages in Africa, and of privilege mobility towards post-tourist areas in the “Global South”. Several entrepreneurial activities, led by European migrants of multiple backgrounds, have stimulated social, economical and cultural dynamics which highlight Saint- Louis’s past as a Euro-African, especially a French-Senegalese heritage. Paradoxically, this image of historical and cultural crossing, which underlies the building of a community beyond social borders and is promoted to encourage local development, induces professional discrepancies, social divide and racial distinctions. This specific image of Saint-Louis’s heritage also directs and selects tourist flows, and contributes to limit economical dynamism. The promotion of cultural tourism thus faces social realities and practices which challenge its initial goals. It produces mechanisms and logics of distinction, revealing a heritage under conflicted pressure, in an economical and urban environment which increases racialized and social asymmetry.